Academic Outcomes Following a School-Based RCT for ADHD: 6-Year Follow-Up. Issue 1 (January 2020) - Sayal, Kapil; Merrell, Christine; Tymms, Peter; Kasim, Adetayo
Objective: For children with high levels of ADHD symptoms, to investigate the impact of early school-based interventions on academic outcomes in mid-childhood.Method: A 6-year follow-up of 4- to 5-year-olds ( N = 52, 075) whose schools participated in a cluster randomized controlled trial for children at risk of ADHD. School-level interventions involved the provision of a booklet with evidence-based information (book) and/or feedback of names (identification) of children with high levels of ADHD symptoms. At ages 10 to 11 years, outcome measures were scores in English and mathematics tests.Results: For children with high levels of ADHD symptoms, the interventions had no impact on academic outcomes. When all children were analyzed, the book intervention had a positive impact on mathematics. Baseline inattention was associated with poorer academic outcomes, whereas impulsiveness was associated with better academic outcomes.Conclusion: The provision of evidence-based information about helping children with ADHD at school may have wider academic benefits.